ANALISIS PENGARUH BI RATE DAN KINERJA KEUANGAN BANK TERHADAP PEMBIAYAAN BANK SYARIAH DI INDONESIA (2010 - 2017) - Didit Suprayitno; Idah Zuhroh; M.Faisal Abdullah (Program Studi Ekonomi Pembangunan, 2019)
This study aims to analyze the influence of the independent variables, namely the BI Rate, Third Party Funds (DPK), Capitalization of Adequacy Ratio (CAR) and Operational Income Costs (BOPO) on Islamic bank financing in Indonesia 2010 - 2017. This type of research is Quantitative Inferential . The required data is secondary data from the financial statements of five Islamic banks in Indonesia 2010-2017.4. Data analysis techniques are panel data regression analysis techniques. The results of the study show that the BI Rate variable has a significant negative effect on financing, Third Party Funds (TPF) have a significant positive relationship to financing, while for the variable Capital Adequacy Ratio (CAR) has a significant positive effect on financing and for Operational Income Operating Costs (BOPO) no significant negative effect on financing. The coefficient of determination (R ^ 2) is 0.938581 or 93.85%. This shows that the ability of the independent variables namely BI Rate, DPK, CAR and BOPO explain the dependent variable of Financing at 93.85% and the remaining 6.15% can be explained by other variables.